THE EFFECT OF GROUP GUIDANCE SERVICES ON STUDENT CONFIDENCE AT SMA NEGERI 5 TIDORE KEPULAUAN - Nurlita Salahuddin; Jasin Taher; Hans F. Pontororing (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2023)
Self-confidence is a positive attitude where an individual is able to develop a positive assessment of himself and the environment or situation he is facing.In developing student self-confidence, counseling teachers carry out group guidance services, by taking advantage of the group dynamics it. The purpose of this study was to determine the effect of group guidance services on student confidence in SMA Negeri 5 Tidore Kepulauan. This research uses quantitative research and random sampling as many as 10& or 43 students of SMA Negeri 5 Tidore Kepulauan from a total of 430. Data were collected through a questionnaire with a likert scale model. The data annalysis technique used simple linear regression analysis with the help of a computer program SPSS 22 for windows. The results showed that there was an effect of group guidance services on student self-confidence at SMA Negeri 5 Tidore Kepulauan by 69,5%, this is also seen from the results of the F test which if F count > F table and sig value < 0,05 then Ha is accepted and Ho was rejected. The conclusion is that the Ha hypothesis which says there is an effect of group guidance services on student confidence in SMA Negeri 5 Tidore Kepulauan is accepted and significant, this is indicated by the value of the regression coefficient (F) of 93.320 with a significance of 0.000